New constraints on the last deglaciation of the Cordilleran Ice Sheet in coastal Southeast Alaska. Issue 1 (July 2020) - Lesnek, Alia J.; Briner, Jason P.; Baichtal, James F.; Lyles, Alex S.
Abstract: Understanding marine-terminating ice sheet response to past climate transitions provides valuable long-term context for observations of modern ice sheet change. Here, we reconstruct the last deglaciation of marine-terminating Cordilleran Ice Sheet (CIS) margins in Southeast Alaska and explore potential forcings of western CIS retreat. We combine 27 new cosmogenic 10 Be exposure ages, 13 recently published 10 Be ages, and 25 new 14 C ages from raised marine sediments to constrain CIS recession. Retreat from the outer coast was underway by 17 ka, and the inner fjords and sounds were ice-free by 15 ka. After 15 ka, the western margin of the CIS became primarily land-terminating and alpine glaciers disappeared from the outer coast. Isolated alpine glaciers may have persisted in high inland peaks until the early Holocene. Our results suggest that the most rapid phase of CIS retreat along the Pacific coast occurred between ~17 and 15 ka. This retreat was likely driven by processes operating at the ice-ocean interface, including sea level rise and ocean warming. CIS recession after ~15 ka occurred during a time of climatic amelioration in this region, when both ocean and air temperatures increased. These data highlight the sensitivity of marine-terminating CIS regions to deglacial climate change.